Psychophysiological response of fighter aircraft pilots in normobaric hypoxia training (2018)
Hypoxia remains the most important hazard in high altitude flights as it is a rare condition presenting itself without consistent symptoms that prevent aircrew from warning in advance. An acute ventilatory response is the mechanism that works to get back oxygen concentration homeostasis, causing hypocapnia and a respiratory alkalosis, which causes breathing muscles fatigue. Some authors have identified previous training on hypoxia contexts as essential to avoid accidents but it is still poor know the effect of hypoxia exposition in the psychophysiological and cognitive functions. We proposed the present study with the aims of to study the effect of hypoxia training in cortical arousal, autonomic modulation and muscle strength. We analysed 3 male fight pilots of the Spanish Army before and after normobaric hypoxia training. The following variables were reported: subjective perceived stress (SPS), rated perceived exertion (RPE), cortical arousal (Critical Flicker Fusion Threshold (CFFT)), isometric handgrip strength, blood oxygen saturation (SaO2 ), heart rate (HR) and spirometry values (forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1 ), peak expiratory flow (PEF)). The effect size (ES) was tested by Cohen’s D. No variable presented significant differences between tests. SPS, RPE, handgrip strength, heart rate and FVC increased after training. FEV1 , PEF, CFFT and SaO2 decreased during the training. These results agreed with previous research in military population. Normobaric hypoxia training produces a decreased tendency in cortical arousal and an increase in perceived effort, stress, and increased tendency in muscular strength. These results can help to find specific training for better prepare fight pilots for hypoxic threats.